Characterization of the sex-dependent myocardial S -nitrosothiol proteome - Shao, Qin; Fallica, Jonathan; Casin, Kevin M.; Murphy, Elizabeth; Steenbergen, Charles; Kohr, Mark J. (American journal of physiology. Heart and circulatory physiology, 2016)
Premenopausal women exhibit endogenous cardioprotective signaling mechanisms that are thought to result from the beneficial effects of estrogen, which we have shown to increase protein S-nitrosylation in the heart. S-nitrosylation is a labile protein modification that increases with a number of different forms of cardioprotection, including ischemic preconditioning. Herein, we sought to identify a potential role for protein S-nitrosylation in sex-dependent cardioprotection. We utilized a Langendorff-perfused mouse heart model of ischemia-reperfusion injury with male and female hearts, and S-nitrosylation-resin-assisted capture with liquid chromatography tandem mass spectrometry to identify S-nitrosylated proteins and modification sites. Consistent with previous studies, female hearts exhibited resilience to injury with a significant increase in functional recovery compared with male hearts. In a separate set of hearts, we identified a total of 177 S-nitrosylated proteins in female hearts at baseline compared with 109 S-nitrosylated proteins in male hearts. Unique S-nitrosylated proteins in the female group included the F 1 F O -ATPase and cyclophilin D. We also utilized label-free peptide analysis to quantify levels of common S-nitrosylated identifications and noted that the S-nitrosylation of sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase 2a was nearly 70% lower in male hearts compared with female, with no difference in expression. Furthermore, we found a significant increase in endothelial nitric oxide synthase expression, phosphorylation, and total nitric oxide production in female hearts compared with males, likely accounting for the enhanced S-nitrosylation protein levels in female hearts. In conclusion, we identified a number of novel S-nitrosylated proteins in female hearts that are likely to contribute to sex-dependent cardioprotection.